2013
DOI: 10.1124/jpet.113.205245
|View full text |Cite
|
Sign up to set email alerts
|

Building a Better Analgesic: Multifunctional Compounds that Address Injury-Induced Pathology to Enhance Analgesic Efficacy while Eliminating Unwanted Side Effects

Abstract: The most highly abused prescription drugs are opioids used for the treatment of pain. Physician-reported drug-seeking behavior has resulted in a significant health concern among doctors trying to adequately treat pain while limiting the misuse or diversion of pain medications. In addition to abuse liability, opioid use is associated with unwanted side effects that complicate pain management, including opioid-induced emesis and constipation. This has resulted in restricting long-term doses of opioids and inadeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…Unlike our previous studies demonstrating that morphine (i.c.v. dosing) results in a positive condition place preference indicative of the potential of rewarding behavior, 47 tat-CBD3 and myr-tat-CBD3 (10 μg in 5 μL, i.c.v.) did not produce a significant increase in total time per chamber (45.7% ± 7.1% and 46.5% ± 5.9%, respectively; P = 0.76) nor a decrease suggesting lack of conditioned place aversion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike our previous studies demonstrating that morphine (i.c.v. dosing) results in a positive condition place preference indicative of the potential of rewarding behavior, 47 tat-CBD3 and myr-tat-CBD3 (10 μg in 5 μL, i.c.v.) did not produce a significant increase in total time per chamber (45.7% ± 7.1% and 46.5% ± 5.9%, respectively; P = 0.76) nor a decrease suggesting lack of conditioned place aversion.…”
Section: Resultsmentioning
confidence: 99%
“…47 Three-chambered rat-conditioned place preference/aversion (CPP/CPA) apparatus (San Diego Instruments, San Diego, CA) with the following modifications were used: (1) end chamber of horizontal black and white striped walls, smooth floor; (2) end chamber of black walls, rough floor; and (3) middle chamber of neutral gray walls and metal rod flooring. Male Sprague-Dawley rats (200–225 g, Harlan) were implanted with intracerebroventricular cannula (i.c.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have demonstrated that these ligands have none of the toxicities associated with morphine long term use including: 1) no motor impairment; 2) no development of tolerance after several days of administration of drug; 3) no development of place preference, an assay for addiction potential after several days of administration; and 4) no inhibition of gut transit (constipation) as well as others [3,4,5].…”
Section: Fig 1 Design Of Mu-delta Opioid Receptor Agonist Nk-1 Recmentioning
confidence: 91%
“…To summarize, our 3 compounds show potent analgesic effects in both acute and neuropathic pain models given i.p. or given i.v., and all three compounds cross the blood brain barrier.In addition, we have demonstrated that these ligands have none of the toxicities associated with morphine long term use including: 1) no motor impairment; 2) no development of tolerance after several days of administration of drug; 3) no development of place preference, an assay for addiction potential after several days of administration; and 4) no inhibition of gut transit (constipation) as well as others [3,4,5].We are very excited about these findings which strongly suggest that this multivalent approach to drug has great potential for the development of novel drugs for the treatment of prolonged pain without toxicities or the development of tolerance, and our approach can find applications to other degenerative diseases. …”
mentioning
confidence: 94%